Experiences and needs of certified nursing assistants regarding coaching by bachelor‐educated registered nurses in nursing homes: A qualitative study - Marieke Van Kuppenveld; Marleen Hermien Lovink; Anke Persoon (Wiley, 2023)
Abstract Aims and objectives This study aimed to gain insight into the experiences and needs of certified nursing assistants regarding their coaching by bachelor‐educated registered nurses in nursing homes. Background Certified nursing assistants are key in providing day‐to‐day nursing home care. They are, however, not trained to meet the increasingly complex needs of nursing home residents. For certified nursing assistants to respond to high‐complexity care, coaching by bachelor‐educated registered nurses may be appropriate. Yet, knowledge of how bachelor‐educated registered nurses can provide valid coaching is lacking. Design An explorative qualitative design was adopted. Methods Certified nursing assistants (n = 13) were purposively selected from 10 Dutch nursing homes. Semi‐structured interviews were conducted in 2020 and 2021, and thematic analysis was applied. Results Two main themes emerged: connecting with certified nursing assistants, and the coaching activities themselves. Certified nursing assistants deemed several aspects important for bachelor‐educated registered nurses to connect with them: respecting the autonomy of certified nursing assistants, being visible and reachable, adapting communication, clarifying own job description, and participating in care. Certified nursing assistants perceived coaching by bachelor‐educated registered nurses as valuable when they fulfil their needs through activities such as empowering, teaching, and mediating between management and certified nursing assistants. Conclusions Valid coaching of certified nursing assistants appears possible and requires specific competencies of bachelor‐educated registered nurses. Relevance to clinical practice Coaching certified nursing assistants is one way of addressing complex care needs in nursing homes, and coaching can contribute to both professional and team development. As coaching requires specific competencies of bachelor‐educated registered nurses, nursing education profiles should be enriched with this most important role. Management can facilitate coaching by providing bachelor‐educated registered nurses with a clear job description. Patient or public contribution Experts on coaching in nursing home settings informed the topic list. Furthermore, member check was performed.